Elite Tennis Players with a Weak Rotator Cuff: The Paradox of Infraspinatus Atrophy - A Clinical Commentary and Practical Approach - Yannick Lambrecht; Leon Philipp Knoche; Lukas Höller (International Journal of Sports Physical Therapy)
Infraspinatus atrophy (IA) is a prevalent but often overlooked condition in elite tennis players, resulting from suprascapular nerve (SN) dysfunction due to repetitive traction or compression. While many athletes maintain normal biomechanics through compensatory mechanisms, these adaptations can lead to kinetic chain imbalances, increasing the risk of secondary injuries. Early detection is crucial to preventing long-term structural changes. Diagnosis involves visual inspection, palpation, and functional tests, though ultrasound imaging offers a more objective assessment of infraspinatus muscle thickness. Conservative treatment aims to restore mobility, strength, and neuromuscular control. Athletes should initially avoid aggravating movements before gradually reintroducing overhead activity. Preventing posterior capsule stiffness through targeted stretching reduces SN compression risk, while nerve gliding exercises enhance mobility. Strengthening programs should prioritize controlled eccentric loading of the infraspinatus and scapular control exercises to improve stability and reduce compensatory strain on surrounding muscles. Preventive strategies are similar to rehabilitation approaches and should be incorporated into training routines, particularly for young athletes. Structured progression in strength training and workload management is essential to prepare the shoulder for high-impact movements like serving. Further research is needed to investigate the relationship between IA and athletic performance, including serve speed and injury risk. This clinical commentary presents a practical approach to the diagnosis and management of IA in elite tennis players. # Level of Evidence 5